2014
DOI: 10.1038/srep05294
|View full text |Cite|
|
Sign up to set email alerts
|

Formation mechanism and optimization of highly luminescent N-doped graphene quantum dots

Abstract: Photoluminescent graphene quantum dots (GQDs) have received enormous attention because of their unique chemical, electronic and optical properties. Here a series of GQDs were synthesized under hydrothermal processes in order to investigate the formation process and optical properties of N-doped GQDs. Citric acid (CA) was used as a carbon precursor and self-assembled into sheet structure in a basic condition and formed N-free GQD graphite framework through intermolecular dehydrolysis reaction. N-doped GQDs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
539
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 819 publications
(574 citation statements)
references
References 38 publications
32
539
1
2
Order By: Relevance
“…Aqueous solutions of GQDs and F-GQDs reveal black and achromatic colors, respectively, under sunlight [25]; Figure 3(a) (inset) shows that GQDs and F-GQDs emit bright yellow and green photoluminescence under irradiation by a 365 nm UV lamp, respectively. The GQDs have a weak absorption at 342 nm, which is close to previous reports [26], and a strong broad absorption at 480 nm, which is in the visible light range. F-GQDs have a typical absorption peak at 337 nm corresponding to the → * transition of the C=O bond.…”
Section: Resultssupporting
confidence: 63%
“…Aqueous solutions of GQDs and F-GQDs reveal black and achromatic colors, respectively, under sunlight [25]; Figure 3(a) (inset) shows that GQDs and F-GQDs emit bright yellow and green photoluminescence under irradiation by a 365 nm UV lamp, respectively. The GQDs have a weak absorption at 342 nm, which is close to previous reports [26], and a strong broad absorption at 480 nm, which is in the visible light range. F-GQDs have a typical absorption peak at 337 nm corresponding to the → * transition of the C=O bond.…”
Section: Resultssupporting
confidence: 63%
“…For instance, Xu et al 28 developed a green heterogeneous synthetic method for NCDs with yellowish-green fluorescence. Qu et al 29 synthesized highly fluorescent blue-emission NCDs with citric acid (CA) and ethylene diamine. In the Qu's work, 30 NCDs prepared with low urea/citric acid mass ratio of 0.2:1 exhibit blue emission, while show green emission when the mass ratio increases to 2:1.…”
mentioning
confidence: 99%
“…In Figure 3, the absorption spectra of the CDs from CA are shown. The absorption band in the UV region at ~340 nm assigned to the n-π* transition [14,22] sharply increases with the reaction time due to the formation of CDs. The contour plots of PL intensities of the CDs from CA with EDA are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…A pair of citric acid (CA) and ethylendiamine (EDA) has been used as the reactants for the pyrolytic and hydrothermal syntheses [14][15][16][17][18], where CA and EDA are the carbon and nitrogen sources. It is noteworthy that an extremely high quantum yield of 0.94 is achieved with the pyrolysis of CA and EDA in autoclave [14]. It is also found that the molecular structures of amines drastically changes the PL properties of the CDs; EDA gives substantially higher quantum yields than other amines such as diethyl-and triethylamines [16].…”
Section: Introductionmentioning
confidence: 99%